2018
DOI: 10.1017/cjn.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in the Management of Central Neuropathic Pain Syndromes: A Prospective Observational Cohort Study

Abstract: Patients with central neuropathic pain syndromes managed in tertiary care centers were less likely to achieve a meaningful improvement in pain and function compared with patients with peripheral neuropathic pain at 12-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
(112 reference statements)
0
6
0
1
Order By: Relevance
“…Indeed, conventional assessment scales such as VAS or NRS predominantly measure the sensory component of pain, whereas the cognitive and affective dimensions remain understudied. Recent research supports that improvement in functional metrics can be dissociated from pain scores; for example, a prospective study of medical management for central neuropathic pain identified a greater proportion of patients achieving a functional improvement as opposed to pain reduction (38.5% vs. 13.5% of patients, respectively) (27). Studies of deep brain stimulation for neuropathic pain have also reported improvements quality of life metrics (e.g., BDI, MPQ) despite inadequate reductions in pain intensity (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, conventional assessment scales such as VAS or NRS predominantly measure the sensory component of pain, whereas the cognitive and affective dimensions remain understudied. Recent research supports that improvement in functional metrics can be dissociated from pain scores; for example, a prospective study of medical management for central neuropathic pain identified a greater proportion of patients achieving a functional improvement as opposed to pain reduction (38.5% vs. 13.5% of patients, respectively) (27). Studies of deep brain stimulation for neuropathic pain have also reported improvements quality of life metrics (e.g., BDI, MPQ) despite inadequate reductions in pain intensity (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, these drugs have many side effects, such as neurocognition, falls, and weight gain [ 18 ]. In addition, the management of neuropathic pain lasts for long-term, and most patients have not enough to relieve pain [ 19 , 20 ]. Therefore, it is particularly urgent and important to investigate more effective and novel therapeutic options for neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of long-term outcomes in the management of CNP show that patients with CNP are less likely to achieve clinically notable improvements in pain relief and function than those with peripheral neuropathic pain [ 16 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies of long-term outcomes in the management of CNP show that patients with CNP are less likely to achieve clinically notable improvements in pain relief and function than those with peripheral neuropathic pain [16]. SCI-related neuropathic pain is associated with a lower response to placebo compared to other neuropathic pain conditions (e.g., HIV neuropathy) [17].…”
Section: Epidemiologymentioning
confidence: 99%